Confabulation affecting Temporal Consciousness significantly more than Knowing Consciousness. (16th March 2020) - Barba, Gianfranco Dalla; Brazzarola, Marta; Marangoni, Sara; Alderighi, Marzia
Abstract: Confabulation, defined as the production of statements and actions that are unintentionally incongruous to the patient's history, background, present and future situation, is a rather infrequent memory disorder, which usually affects patients with significant memory impairment, but may be also observed in patients with normal memory and learning abilities. Confabulation may be selective affecting some cognitive, memory domains while relatively sparing others. In particular, it may affect more Temporal Consciousness, i.e. a specific form of consciousness that allows individuals to remember their personal past, to be oriented in their present world and to predict their personal future, than Knowing Consciousness, i.e. a specific form of consciousness allowing individuals to be aware of past, present and future impersonal knowledge and information. In this study we evaluated confabulations in TC and KC in a group of confabulatory amnesics of various aetiologies. Based on previous studies, it was predicted that confabulations affect significantly more TC than KC. It was also predicted that "Habits Confabulations", i.e. habits and repeated personal events mistaken as specific, unique past and future personal episodes, is the more frequently observed type of confabulation. The results confirmed these predictions and are discussed within the framework of the Memory, Consciousness and Temporality Theory. Highlights: Confabulation affects more Temporal Consciousness than Knowing Consciousness. "Habits Confabulations" is the more frequently observed type of confabulation. Confabulation is not associated with any specific brain lesion.